Using crop analysis in the precision nutrient supply system of maize - Izsáki, Zoltán (Acta Agraria Debreceniensis, 2012)
The effect of the N, P and K supplies of soil on the grain yield and N, P and K status of maize was studied in a long-term mineral fertilisation experiment between 2001 and 2008 and nutrient supply limit values were determined to plant analysis. Based on the interaction between the N concentrtion of maize leaves measured at the beginnig of tasseling and grain yield, the satisfactory limit value of N supply to reach 10–14 t ha-1 yield was between 2.0–4.0%. Leaf analysis at the beginning of tasselling indicated that better P and K supplies were associated with a higher P and K concentration in the maize leaves. Correlation analysis on the P concentration of the maize leaves and the grain yield showed that at a grain yield level of 10–14 t ha-1 a P concentration of 0.20–0.37% represented a satisfactory P supply level. The satisfactory K supply limit value to reach 10–14t ha-1 grain yield was 1.5–2.6%.